Nilai-Nilai Pendidikan Kultural dalam Dakwah Susuhunan Kalijaga - Waskito, Puthut (LPPM STAI Ihyaul Ulum Gresik, 2019)
The spread of Islam in Java has a unique history. This uniqueness is because the people of the interior of Java do not necessarily accept the teachings of Islam in a kaffah manner. This is because the people of the interior of Java already have a high culture in the spiritual field. Therefore, Susuhunan Kalijaga carried out an Islamic missionary mission known as jalasutra. In this mission, Susuhunan Kalijaga uses a cultural approach with a moderate and tolerant attitude towards the culture and various thoughts of the local community. There are various ways Susuhunan Kalijaga performs Islamic da'wah in the interior of Java, namely by performing shadow puppets; Sekaten gamelan performances on Islamic holidays; incorporate Islamic values ​​into Javanese kebatinan teachings; opening a place for Islamic religious education with a hermitage style; teaches mask dance; wrote sharing books of fiber, suluk, primbon, and song; preaching to state officials as an implementation of the philosophy of agomo ageming aji; perform ritual activities of tahlil, genduri, syi'iran, and gembrungan. These various methods have had a positive impact on the development of the spread of Islam in the interior of Java.